Current Development and Challenges of Tetravalent Live-Attenuated Dengue Vaccines - Hou, Jue; Ye, Weijian; Chen, Jianzhu (Frontiers in Immunology, 2022)
Dengue is the most common arboviral disease caused by one of four distinct but closely related dengue viruses (DENV) and places significant economic and public health burdens in the endemic areas. A dengue vaccine will be important in advancing disease control. However, the effort has been challenged by the requirement to induce effective protection against all four DENV serotypes and the potential adverse effect due to the phenomenon that partial immunity to DENV may worsen the symptoms upon subsequent heterotypic infection. Currently, the most advanced dengue vaccines are all tetravalent and based on recombinant live attenuated viruses. CYD-TDV, developed by Sanofi Pasteur, has been approved but is limited for use in individuals with prior dengue infection. Two other tetravalent live attenuated vaccine candidates: TAK-003 by Takeda and TV003 by National Institute of Allergy and Infectious Diseases, have completed phase 3 and phase 2 clinical trials, respectively. This review focuses on the designs and evaluation of TAK-003 and TV003 vaccine candidates in humans in comparison to the licensed CYD-TDV vaccine. We highlight specific lessons from existing studies and challenges that must be overcome in order to develop a dengue vaccine that confers effective and balanced protection against all four DENV serotypes but with minimal adverse effects.